2021
DOI: 10.4314/jae.v25i4.5
|View full text |Cite
|
Sign up to set email alerts
|

Workplace conflict and employees’ job performance in Agro-services Corporation, Ogun State, Nigeria

Abstract: The study determined the effects of workplace conflict on employees’ job performance in Ogun State Agro-service Corporation (OGASC). Multistage sampling technique was used to select 77 respondents. Data were collected through the administration of questionnaires and were analysed using frequency, percentage, and mean. The presence of functional staff union to minimize conflict (x̅ = 2.99) ranked as the first indication of reduced conflict, followed by existence of favouritism (x̅ = 2.51) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
2
1
Order By: Relevance
“…The study support Suprapto and Widigdo, (2021) who revealed that conflict has a partial negative impact on employee performance and is not significant. The finding contradicts the study of Ayinde et al (2021) who revealed that job performance of the respondents was not adversely affected by the workplace conflict they experienced. It also supported the findings of El Dahshan&Keshk, (2014) who revealed that interpersonal conflict strategies, relationship conflict and task conflict significantly affect organizational performance.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…The study support Suprapto and Widigdo, (2021) who revealed that conflict has a partial negative impact on employee performance and is not significant. The finding contradicts the study of Ayinde et al (2021) who revealed that job performance of the respondents was not adversely affected by the workplace conflict they experienced. It also supported the findings of El Dahshan&Keshk, (2014) who revealed that interpersonal conflict strategies, relationship conflict and task conflict significantly affect organizational performance.…”
Section: Discussioncontrasting
confidence: 90%
“…The study revealed that workplace conflict impacts employee performance through increased absenteeism, turnover, and decreased employee wellbeing. However, the findings show that task conflicts have a significant, positive connection to employee performance, and relationship and process conflicts negatively affects employee performance Ayinde, Bolarinwa, Alarima, Kazeem, and Kareem (2021) examined effects of workplace conflict on employees' job performance in Ogun State Agro-service Corporation (OGASC). The study showed that presence of functional staff union to minimize conflict ( =2.99) ranked as the first indication of reduced conflict, followed by existence of favouritism ( = 2.51) which was ranked highest as an indication of conflict escalating factor by the respondents.…”
Section: Introductionmentioning
confidence: 99%
“…Conflict is one of the most predictable results of group collaboration. Most managers spend a large portion of their working hours resolving disputes or the consequences of issues with people (Ayinde et al, 2021). According to Nnam (2013), concern has been raised about the importance and role of conflict in organisations.…”
Section: Introductionmentioning
confidence: 99%